One-step synthesis of high quality kesterite Cu2ZnSnS4 nanocrystals – a hydrothermal approach - Tiong, Vincent Tiing; Bell, John; Wang, Hongxia (Beilstein Journal of Nanotechnology, 2014)
The present work demonstrates a systematic approach for the synthesis of pure kesterite-phase Cu2ZnSnS4 (CZTS) nanocrystals with a uniform size distribution by a one-step, thioglycolic acid (TGA)-assisted hydrothermal route. The formation mechanism and the role of TGA in the formation of CZTS compound were thoroughly studied. It has been found that TGA interacted with Cu2+ to form Cu+ at the initial reaction stage and controlled the crystal-growth of CZTS nanocrystals during the hydrothermal reaction. The consequence of the reduction of Cu2+ to Cu+ led to the formation Cu2−xS nuclei, which acted as the crystal framework for the formation of CZTS compound. CZTS was formed by the diffusion of Zn2+ and Sn4+ cations to the lattice of Cu2−xS during the hydrothermal reaction. The as-synthesized CZTS nanocrystals exhibited strong light absorption over the range of wavelength beyond 1000 nm. The band gap of the material was determined to be 1.51 eV, which is optimal for application in photoelectric energy conversion device.
Keywords: Cu2ZnSnS4 nanocrystals; formation mechanism; hydrothermal; thioglycolic acid